The platform economy and the smart city : technology and the transformation of urban policy - Zwick, Austin; Spicer, Zachary, 1983- (McGill-Queen's studies in urban governance, 2021)
"Over the past decade, cities have come into closer contact and conflict with new technologies. From reactive policymaking in response to platform economy firms to proactive policymaking in an effort to develop into smart cities, urban governance is transforming at an unprecedented speed and scale. Innovative technologies promise a brave new world of convenience and cost effectiveness--powered by cameras that monitor our movements, sensors that line our streets, and algorithms that determine our resource allocation--but at what cost? Exploring the relationship between technology and cities, this book brings together an outstanding group of authors in the field to provide a critical and necessary examination of the disruption that is under way. They look at how cities should understand and regulate novel technologies, what can be learned from proposed and failed smart city projects, and how innovative economies change the structure of cities themselves. Contributors dig deeply into these and similar subjects, contributing their voices to an important dialogue on the future of urban policy and governance. The first collection of its kind, this groundbreaking volume brings together social, economic, and cultural insights to enhance our understanding of the ongoing technological upheaval in cities around the world."--